Comparison of 2 pupil expansion devices for small‐pupil cataract surgery. Issue 8 (August 2016) - Tian, Jack J.; Garcia, Giancarlo A.; Karanjia, Rustum; Lu, Kenneth L.
Abstract : N/A: We compared the degree of postoperative iris distortion with the diamond‐shaped Malyugin ring and the circular Visitec I‐Ring iris dilators using postoperative iris photographs in a patient with bilateral small nondilating pupils. Routine phacoemulsification was performed in the right eye with the assistance of a Malyugin ring for iris dilation. One month later, the same procedure was performed in the left eye using the circular ring for iris dilation. Anterior chamber slitlamp photographs were taken of both eyes. The amount of distortion in the postoperative pupils was calculated using the ratio of the postoperative pupil area to the area of the circle of best fit. The circular ring, constructed from a softer material, resulted in 11% distortion and the Malyugin ring, 49%, suggesting that the circular ring caused less trauma to the iris. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.